Investigating Joint Market Hypothesis during Periods of Financial Distress and its Implications - Enow, Samuel Tabot (International Journal of Economics and Financial Issues, 2023)
Empirical finance is about building an understanding of security prices and financial markets so as to foster better decision making while avoiding anecdote biases. Successful investors are often cognisant of their risk exposures coupled with extreme discipline and leverage. Therefore, the aim of this study was to explore the concept of joint market hypothesis in five international stock indexes. This study used the Taleb’s ratio which is an extension of the Parkinson model. The financial distress periods were the financial crisis (December 1, 2007 to June 30, 2009) and the Covid-19 pandemic (January 1, 2020 to December 31, 2021). Joint hypothesis was evident in the JSE, CAC 40, the DAX and the Nikkei 225 while the Nasdaq displayed high levels of market efficiencies. Allocating more capital to the JSE, CAC 40, the DAX and the Nikkei 225 during periods of financial distress in conjunction with the Fama French five factor model will generate higher returns. As per the author’s knowledge, this study is the first to explore the concept of joint market hypothesis during periods of distress